Significant contribution of metastable particulate organic matter to natural formation of silver nanoparticles in soils - Huang, Ying-Nan (2019)
Particulate organic matter (POM) is distributed worldwide in high abundance. Although insoluble, it could serve as a redox mediator for microbial reductive dehalogenation and mineral transformation. Quantitative information on the role of POM in the natural occurrence of silver nanoparticles (AgNPs) is lacking, but is needed to re-evaluate the sources of AgNPs in soils, which are commonly considered to derive from anthropogenic inputs. Here we demonstrate that POM reduces silver ions to AgNPs under solar irradiation, by producing superoxide radicals from phenol-like groups. The contribution of POM to the naturally occurring AgNPs is estimated to be 11–31%. By providing fresh insight into the sources of AgNPs in soils, our study facilitates unbiased assessments of the fate and impacts of anthropogenic AgNPs. Moreover, the reducing role of POM is likely widespread within surface environments and is expected to significantly influence the biogeochemical cycling of Ag and other contaminants that are reactive towards phenol-like groups.